The Spanish-Version of the Subjective Vitality Scale: Psychometric Properties and Evidence of Validity. (5th June 2017) - Castillo, Isabel; Tomás, Inés; Balaguer, Isabel
Abstract: The Subjective Vitality Scale (SVS) assess the subjective experience of being full of energy and alive, a clinically relevant outcome measure of positive psychological well-being. The purpose of this paper was to translate the 7-item SVS into Spanish and examine its psychometric properties. In Study 1 ( n = 790 adolescents) and Study 2 ( n = 130 athletes) reliability and exploratory factor analysis (EFA) were carried out. In Study 1 and Study 3 ( n = 197 dancers) evidence of validity of inferences based on SVS scores estimating relationships with other variables (life satisfaction, global self-esteem and emotional and physical exhaustion) was obtained. In Study 2 invariance across time was tested. Finally in Study 3, the factorial structure was cross-validated using confirmatory factor analysis (CFA). Results of EFA showed a one-factor solution. CFA also supported a unidimensional factor structure for the Spanish 6-item SVS (RMSEA = .050 (90% CI = .00, .080); NNFI = .993; CFI = .996). Reliability analysis indicated a strong internal consistency in all study samples (α ranged from .82 to .89). Further, results from multi-sample analysis supported the replicability of SVS factor structure across time. Finally, the SVS scores showed the expected correlations patterns (all them significant, p < .01) with the measured outcomes. In conclusion, the Spanish version of the SVS demonstrated adequate psychometric properties, indicating that the scale can be confidently used to measure the experience of possessing energy and aliveness; furthermore, differences across time can be meaningfully carried out.